2014
DOI: 10.1186/1471-2490-14-103
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between penile cuff test and pressure-flow study in patients candidates for trans-urethral resection of prostate

Abstract: BackgroundAim of this study was to make a comparison between penile cuff test (PCT) and standard pressure-flow study (PFS) in the preoperative evaluation of patients candidates for trans-urethral resection of prostate (TURP) for benign prostatic obstruction (BPO).MethodsWe enrolled male patients with lower urinary tract symptoms candidates for TURP. Each of them underwent a PCT and a subsequent PFS. A statistical analysis was performed: sensitivity (SE), specificity (SP), positive predictive value (PPV), negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Although the NPV was very high, the PPV was unfortunately not. Similarly, prior studies have found high NPV values (∼88‐100%), but variable PPV values (66.7‐82%) …”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Although the NPV was very high, the PPV was unfortunately not. Similarly, prior studies have found high NPV values (∼88‐100%), but variable PPV values (66.7‐82%) …”
Section: Discussionsupporting
confidence: 71%
“…There are limited data regarding the relationship between PCT and PFS results . In addition, the role of PCT in clinical practice has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, the diagnostic accuracy was high, with median sensitivity of 88% and specificity of 70%. There was low RoB across most studies, but significant heterogeneity in the threshold values used to diagnose BOO, with three studies using the nomogram developed by Griffiths et al [11,18,22], two using different nomograms [32,42], and two using a penile urethral compression-release index of either [7] 102 NRE Uroflowmetry 10 ml/s NR LPURR >2 or >3 LPURR>2 + URA >29 Q max <15 and P det Q max >50 [47] 87 NRE NIRS NIRS algorithm Yes BOOI >40 Uroflowmetry + PVR 10 ml/s and 100 ml BOOI = bladder outflow obstruction index; BOON = BOO number; BSA = body surface area; BWT = bladder wall thickness; CART = classification and regression tree; DWT = detrusor wall thickness; DAMPF = detrusor-adjusted mean PURR factor; ICS = International Continence Society; LPURR = linear passive urethral resistance relation; MLL = middle lobe length; NRE = nonrandomised experimental; NIRS = near-infrared spectroscopy; NR = not reported; NPV = negative predictive value; PCR = penile compression ratio; PCT = penile cuff test; P det Q max = detrusor pressure at Q max ; P ext max = maximum external pressure; PPV = positive predictive value; Pts = patients; Q max = maximum flow; RI = resistive index; RS = retrospective; UEBW = ultrasound-estimated bladder weight; URA = urethral resistance algorithm; VPG = voiding profilometry gradient across the bladder neck and prostatic urethra in the absence of distal obstruction; VR = velocity ratio.…”
Section: Diagnostic Accuracy Resultsmentioning
confidence: 99%